Her2 promotes early dissemination of breast cancer by inhibiting the p38 pathway through the downregulation of MAP3K4 - Guanwen Wang; Ping Wen; Ting Xue; Yuxin Huang; Qing Shao; Ningning Zhang; Fanli Qu; Jing Wang; Nan Wang; Xiaohua Zeng (Cell Communication and Signaling)
Abstract Early dissemination refers to the process by which cancer cells spread to distant organs at an early stage of the disease, often before the primary tumor is clinically detectable. Experimental studies have demonstrated that Her2 promotes early dissemination of breast cancer by inhibiting the p38 signaling pathway. However, the precise mechanism by which Her2 suppresses the activation of p38 signaling in early-stage cancer cells (ECCs) remains unclear. Here, we report that MAP3K4, an upstream kinase of p38, is downregulated in Her2 + ductal carcinoma in situ (DCIS) cells and tissues, which is required for Her2-induced early dissemination of DCIS cells by regulating the activation of the p38 signaling cascade. Furthermore, Her2 suppresses the transcription of MAP3K4 by downregulating the expression of HOXB13, a crucial transcription factor contributing to MAP3K4 expression in DCIS cells. Together, these findings unveil a novel downstream regulatory mechanism through which Her2 inhibits the activation of p38 signaling and facilitates early dissemination of breast cancer, offering insights into the development of effective diagnostic methods and targeted therapies for inhibiting the early dissemination of Her2 + breast cancer.